(E)-1-(3-Bromophenyl)-3-(4-nitrophenyl)prop-2-en-1-one - Harini, K. S.; Ching, Kheng Quah; Chidan Kumar, C. S.; Chandraju, S.; Lokanath, N. K.; Naveen, S.; Warad, Ismail (International Union of Crystallography, 2017)
The title compound, C15H10BrNO3, is close to planar, as seen by the dihedral angle of 3.32 (17)° between the bromophenyl and nitrophenyl rings. In the crystal, molecules are linked by weak C—H...O hydrogen bonds, forming chains propagating along the c-axis direction.